The Inverted Fisher Hypothesis : Inflation Forecastability and Asset Substitution" - Choi, Woon. (Washington, D.C. : International Monetary Fund, 2000)
This paper examines the implications of inflation persistence for the inverted Fisher hypothesis that nominal interest rates do not adjust to inflation because of a high degree of substitutability between money and bonds. It is emphasized that the substitutability between nominal assets and capital renders the hypothesis inconsistent with the data when inflation persistence is high. Using a switching regression model, the analysis allows the reflection of inflation in interest rates to vary according to the degree of inflation persistence or forecastability. The hypothesis is supported by U.S. data only when inflation forecastability is below a certain threshold.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet